Plant Cell and Tissue Culture - A Tool in Biotechnology Basics and Application - Imani, Jafargholi. (Principles and Practice,, 2009)
This book provides a general introduction as well as a selected survey of key advances in the fascinating field of plant cell and tissue culture as a tool in biotechnology. After a detailed description of the various basic techniques employed in leading laboratories worldwide, follows an extended account of important applications in, for example, plant propagation, secondary metabolite production and gene technology. Additionally, some chapters are devoted to historical developments in this domain, metabolic aspects, nutrition, growth regulators, differentiation and the development of culture systems. The book will prove useful to both newcomers and specialists, and even "old hands" in tissue culture should find some challenging ideas to think about.